BIOLOGIA DA OCUPAÇÃO DE CONCHAS POR ERMITÕES (CRUSTACEA, DECAPODA, ANOMURA) PROVENIENTES DA PRAIA DA SEPULTURA, BOMBINHAS, SC - Vieira, Neida Rodrigues (2019)
The hermits are decapod crustaceans that occupy shells as protection for their decalcified abdomen. The distribution and survival of these animals is determined by the availability of shells in the environment. Thus, the occupation of gastropod mollusc shells by different species of hermitages, on the beach of La Sepultura, Bombinhas, SC, was investigated in the present study. The species of hermits and the shells that each one occupied were identified, as well as the percentages of the types of shells that were occupied and the morphometric relationships between the crustaceans and shells, from four collections over a year. The individuals were identified and classified into males, females, ovigerous and intersex females, weighed (WW= wet weight) and measured in relation to the length (SL) and width (SW) of the cephalothoracic shield. The shells were identified, measured in relation to the width of the aperture (SAW), length of the aperture (SAL) and dry weight (DW). An interaction network between hermit species and shells was elaborated. A total of 1,328 hermits were collected from the species: Pagurus bravidactylus (1,021), Pagurus criniticornis (243), Dardanus insignis (19), Calcinus tibicen (18), Paguristes tortugae (15) and Clibanarius antillensis (12). The hermitages occupied shells of 26 species of gastropod molluscs. Cerithium atratum and Morula nodulosa were the most commonly used by P. brevidactylus and P. criniticornis. Dardanus insignis occupied Astralium latispina. Pisania pusio was the species most occupied by C. tibicen. Paguristes tortugae frequently inhabited Leucozonia nassa. Clibanarius antillensis were found occupying C. atratum. The coefficients of determination (r2) varied between the species of hermits and the occupied shells, which is an important indication that different species occupied shells appropriate to their size. The network of interaction between the hermits and the occupied shells, was generalist. The high number of species of shells used and the relative plasticity in the pattern of selection of shells by the individuals indicated that the occupation is influenced by the availability of shells and better corporal adequation of the hermits.